LEGAL CAPACITY ASEN DALAM PENYELESAIAN SENGKETA LAUT CHINA SELATAN - Arbi Nurcahyanto (Jurnal HUKUM BISNIS, 2020)
The advisory opinion of the International Court states that de jure and de facto it is sufficient for the United Nations as an international organization that has the legal personality and legal capacity to act before the law representing the interests of the UN itself as well as the interests of its victims. ASEAN has a legal personality implicitly stipulated in article 3 of the ASEAN Charter. Based on this legal personality, the researcher examines ASEAN's legal capacity as a subject of international law and ASEAN's position in resolving South China Sea disputes. By using a conceptual approach and a comparative approach method. That ASEAN has a legal capacity as a subject of international law. ASEAN has the legal capacity to resolve South China Sea disputes between its member countries and has the right to submit international complaints to an international court with the approval of its member countries. Keywords: Legal Capacity, ASEAN, International Organizations, International Dispute Resolution